Analisis Karakter Sosial Pada Teks Cerita Dalam Buku Tematik Kelas V SD/MI Tema Sehat Itu Penting - Nurhazannah, Sari Yulia; Musaddat, Syaiful; Setiawan, Heri (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The problems revealed in this study are 1) How are the forms of Social Characters contained in the Text of the Story in the Thematic Book of Grade V SD/MI The Healthy Theme is Important, and 2) How is the suitability of the Social Character in the Thematic Book for Grade V SD/MI Healthy Theme It is important with the demands of the curriculum. The purpose of this study was to find out the forms of Social Characters in Story Texts in the Thematic Book of Healthy Themes and the suitability of Social Characters in Story Texts in Class V Thematic Books. Healthy themes were important to the demands of the curriculum. This type of research is descriptive qualitative. The population in this study were all story texts contained in the Thematic Book of Class V SD/MI The Healthy Is Important Theme. The sample used was 5 story texts contained in the thematic book for class V SD/MI The Healthy Is Important. Data collection techniques using documentary studies. Based on the results of the discussion, it is known that, 1) In the text of the story contained in the thematic book for grade 5 SD/MI, the Healthy Theme is Important contains social characters: Honest, Sportive, Tolerance, Discipline, Independent, Responsibility, Appreciating achievement, Caring about cleanliness, Caring for health , Friendly / communicative, 2) The social characters contained in the story text in the Thematic book Class V The Healthy Theme is Important shows that it is in accordance with the demands of the curriculum.